1985
DOI: 10.1128/jb.162.1.353-360.1985
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of hydrogenase genes and fine structure analysis of an operon essential for H2 metabolism in Escherichia coli

Abstract: Escherichja coli has two unlinked genes that code for hydrogenase synthesis and activity. The DNA fragments containing the two genes (hydA and hydB) were cloned into a plasmid vector, pBR322. The plasmids containing the hyd genes (pSE-290 and pSE-Ill carrying the hydA and hydB genes, respectively) were used to genetically map a total of 51 mutant strains with defects in hydrogenase activity. A total of 37 mutants carried a mutation in the hydB gene, whereas the remaining 14 hyd were hydA. This complementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…In our case, however, the mutant patterns of hybridizing bands were identical to that of the parent strain (data not shown). Therefore, it was concluded that the gene carried on pHG1O is not identical to hydL, F, or C. It is probably also not identical to hydA, B, or E, since these genes have been cloned and their physical maps do not show homology (9,16,34,44). The gene carried on pHG1O was apparently a new one and was designated hydG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, however, the mutant patterns of hybridizing bands were identical to that of the parent strain (data not shown). Therefore, it was concluded that the gene carried on pHG1O is not identical to hydL, F, or C. It is probably also not identical to hydA, B, or E, since these genes have been cloned and their physical maps do not show homology (9,16,34,44). The gene carried on pHG1O was apparently a new one and was designated hydG.…”
Section: Resultsmentioning
confidence: 99%
“…Some (regulatory) genes such as hydA (16,34), hydB (9,34,44), and hydE (9) have been cloned. This approach has been shown to be fruitful in the study of other gene clusters, e.g., the nif (14), nar (40), or frd (15) operons.…”
mentioning
confidence: 99%
“…These mutations were named ant (anaerobic electron transport) because they were thought to be distinct from hyd; however, genetic mapping reveals an order of cysC-mutS-ant-srl-recA-nalB (435). Therefore, ant and hyd are tightly linked, but apparently not identical (335); that the ant insertion mutations span 5 kilobases indicates that this region contains more than one gene (435).…”
Section: Genetics Of Hydrogenasementioning
confidence: 99%
“…Genetic mapping and complementation analyses with cloned DNA fragments indicate that these mutations define two linked, yet distinct regions termed hydA and hydB. Additional complementation studies with subclones indicates that hydB may include genes required for formate dehydrogenase-H (fdv) and formate-hydrogen lyase (fh1) activities (335). Alterations of fdv would provide an explanation for the lowered formate dehydrogenase-H activity observed in many hyd mutants.…”
Section: Genetics Of Hydrogenasementioning
confidence: 99%
See 1 more Smart Citation